Surgical Treatment of Epilepsy: 40 Years Experience - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The results of surgical treatment between 1940 and 1980 of 118 children with frontal or temporal lobe epilepsy were reviewed at the Montreal Neurological Institute.